National expert consensus on home-administered oncologic therapies in Spain - Villegas, Eulalia; Arruñada, María; Casado, Miguel Ángel; González, Sonia; Moreno-Martínez, María Estela; Peñuelas, María Ángeles; Torres, Ana Maria; Sierra, Yanik; Seguí, Miguel Angel (Frontiers in Oncology, 2024)
Cancer diagnosis and treatment carry a significant emotional and psychological burden on patients and their families/caregivers. Home-based chemotherapy initiatives have emerged as a viable and safe patient-centered model of care that can increase patient comfort and convenience while reducing costs and hospital overload. These home-based care programs have been piloted globally, demonstrating to be a preferred option for most patients without reducing the efficacy and safety of the therapy. However, the available literature exploring drug administration at home in oncology patients is still limited and controversial. Therefore, the present document aims to review the most relevant aspects to be considered during the development and implementation of home chemotherapy programs, and to establish minimum recommendations for the home administration of oncologic therapies based on a national expert agreement.